TO MODELATE OR NOT TO MODELATE: THAT IS NOT THE QUESTION. IS THERE SOMETHING INTERMEDIATE? (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
The present paper tries to show that in the discussion on whether it is better to model or not, to capture truth in the social world, that is not what is mainly being discussed. We put forward that the main question in this discussion is, essentially, ontological, notmethodological. As a representative of the “to model position” we will refer to Uskali Mäki’s Possible Realism, and as one of the “not to model position” we will consider Tony Lawson’s Critical Realism. What will be argued is that the main differences between these positions as regards methodology to access the social world, lie in the different ontologies about the social realm. It will also be introduced if there is any possibility of an “in between position”, or at least the chance of a dialogue between these different epistemological trends.
Keywords: possible realism; critical realism; methodology; ontology; in between position